2016
DOI: 10.1097/npt.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Theory-Based Intervention to Increase Clinical Measurement of Reactive Balance in Adults at Risk of Falls

Abstract: Although future research will evaluate the intervention in a controlled study, the process of theory-based intervention development can be applied to other rehabilitation research contexts, maximizing the impact of this work.Video Abstract is available for more insights from the authors (see Supplemental Digital Content 1, http://links.lww.com/JNPT/A123).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…All of these studies found that this type of training lowered fall risk, but they also all included sophisticated laboratory equipment that is not accessible or practical for most clinicians. This reason, along with the fact that many studies utilized kinematics and spatiotemporal characteristics as outcomes rather than standardized, functional, outcome measures, support previous research that has determined that effective balance reactions are 23 not regularly measured or utilized in interventions by physical therapists.…”
Section: Introductionmentioning
confidence: 62%
“…All of these studies found that this type of training lowered fall risk, but they also all included sophisticated laboratory equipment that is not accessible or practical for most clinicians. This reason, along with the fact that many studies utilized kinematics and spatiotemporal characteristics as outcomes rather than standardized, functional, outcome measures, support previous research that has determined that effective balance reactions are 23 not regularly measured or utilized in interventions by physical therapists.…”
Section: Introductionmentioning
confidence: 62%
“…Initial published intervention components [ 28 ] included using regular health record audits as an additional feedback strategy to participants. However, this component was not delivered due to feasibility challenges extracting participant-linked data in real-time during the intervention.…”
Section: Resultsmentioning
confidence: 99%
“…This study is among the first to use a determinant framework, and more specifically, the TDF, to directly link barriers and facilitators to rehabilitation intervention components, strategies and outcomes. The hands-on practice meeting – the most positively rated component by participants – suggests that rehearsal of relevant skills, feedback, problem solving, decision making, goal setting, and modeling/demonstration of behaviors by others [ 28 , 32 ] may be related to intervention effects. However, this cannot be confirmed in the absence of an appropriate comparator for this intervention.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations